Regulation of a major microtubule-associated protein by MPF and MAP kinase. - Shiina, N (1992)
The interphase-M phase transition of microtubule dynamics is thought to be induced by phosphorylation reactions mediated by MPF and by MAP kinase functioning downstream of MPF. We have now identified and purified from Xenopus eggs a major microtubule-associated protein, p220, that may be a target protein for these two M phase-activated kinases. p220, when purified from interphase cells, potently bound to microtubules and stimulated tubulin polymerization, whereas p220 purified from M phase cells showed little or no such activities. Cell staining with a monoclonal anti-p220 antibody revealed that p220 is localized on cytoplasmic microtubule networks during interphase, while it is distributed rather diffusely throughout the cell during M phase. We have further found that p220 is phosphorylated specifically in M phase. Moreover, p220 purified from interphase cells served as a good substrate for MAP kinase and MPF in vitro, and two-dimensional phosphopeptide mapping pattern of the p220 phosphorylated in vitro was very similar to that of p220 phosphorylated at M phase in vivo. These results suggest that the drastic change in p220 activity during the transition from interphase to M phase may be induced by its phosphorylation in M phase probably catalyzed by MAP kinase and MPF.